IMPLEMENTASI KEBIJAKAN PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN BANYUASIN - Azzuhri, Hatta; Darmawan , Erik; Apriani, Reni (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This research focuses on the implementation of forest and land fire prevention policies in Banyuasin Regency. This research aims to examine the implementation of forest and land fire prevention policies in the Banyuasin Regency area. This research applies a qualitative approach to analyze the implementation of forest and land fire prevention policies in Banyuasin Regency. The results of this research, the success of the implementation of forest and land fire prevention policies in Banyuasin Regency can be seen from the decrease in the number of hotspots in 2016 when compared to 2015. This decrease occurred due to good cooperation between the Regency government, the South Sumatra Provincial Government, Manggala Agni Daops Banyuasin, the community, and other related parties in efforts to prevent forest and land fires in the Banyuasin Regency area. In addition, the establishment of several villages that care about fires in the Banyuasin Regency area and the high community response in efforts to prevent forest and land fires. Obstacles in preventing forest and land fires are mainly related to communication and transportation access. Meanwhile, factors that support the prevention of forest and land fires are the availability of equipment and human resources ready to help prevent forest and land fires.